Beyond Ritual Formalism: Islamic Existential Pedagogy and The Ontology of Care - Mohamad Ali; M Mukalam; Muhamad Subhi Apriantoro (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study aims to reconstruct the ontological foundation of K.H. Ahmad Dahlan's Al-Ma'un Theology by employing Martin Heidegger's concept of Sorge (care), while formulating its implications for the direction of contemporary Islamic education. The study is motivated by the tendency of Islamic education to become ensnared in ritual formalism and mere cognitivism, thereby losing its transformative power. Utilizing a descriptive-analytical method with an existential phenomenological approach, this research finds that Al-Ma'un Theology is not merely a philanthropic doctrine, but a manifestation of "authentic existence." K.H. Ahmad Dahlan (1868-1923) positions amal (social action) as a mode of human "care" (Sorge) toward the world, which is ontologically equivalent to the human endeavor to transcend the meaningless crowd (Das Man). The fundamental implications for Islamic education encompass three aspects: the repositioning of educators as facilitators of the students' self-disclosure; a shift in curriculum orientation from textual mastery toward social praxis; and a definition of educational success measured through the active engagement of the subject in solving humanitarian problems. This research concludes that Al-Ma'un-Heideggerian-based Islamic education is a humanizing pedagogy realized through concrete action within the reality of the world